Buried pipe response subjected to traffic load experimental and numerical investigations - Mosadegh, A.; Nikraz, Hamid (The Geomate International Society, 2017)
In this paper, a flexible buried pipe response subjected to traffic load is investigated through laboratory experiments and numerical analysis. A series of laboratory tests and numerical simulations were carried out to investigate the impact of surface pressure and burial depth on the model response. Experimental tests were carried out using UTM25 to apply load on surface of a tank in which pipe was buried. Numerical simulations were conducted using the Finite Element Method, ABAQUS software to develop a better understanding of the pipe behavior. Results indicate that a good agreement between numerical and experimental test results was observed. In addition, experimental and numerical analysis reveal that increasing burial depth decreases pipe deflection, increases soil surface settlement and decreases pressure on pipe while increasing surface pressure increases all mentioned parameters. From all numerical and experimental results and using the Curve Fitting analysis in Matlab, equations were developed to predict soil surface settlement, pipe vertical diametric strain and pressure on pipe. Cumulative error analysis shows that all predicted parameters have less than 10% error.